Public Service Management Policy According to the Local Development Plan under the National Strategy of Khon Kaen Provincial Administrative Organization - Klunplin, Phoothada (Dhammathas Academic Journal, 2021)
The objectives of this research were: 1) to study the policy of public service provision according to Local Development Plan under the National Strategy of the Khon Kaen Provincial Administrative Organization, 2) to study the problems and opinions in the provision of public services under the Local Development Plan under the National Strategy, 3) Public services according to the local development plan under the National Strategy. It is a mixed method research between quantitative research from a questionnaire, a sample of 400 people, and qualitative Research from an indepth interview with 24 key informants using the target group selection method. In this research using a snowball selection by selecting people with knowledge Understanding of the preparation of local development plans National strategy and public service organization of the Provincial Administrative Organization. The results of the research found that: 1. Public Service Management Policy of Khon Kaen Provincial Administrative Organization there has been a link and integration of the government sector, that is, the administration policy of the Provincial Administrative Organization has been established. according to the powers, duties and guidelines for organizing the public service system of the Khon Kaen Provincial Administrative Organization in accordance with the government policy 20-year national strategy, national economic and social development plan, regional development plan, provincial group development plan provincial development plan and the development strategy of Khon Kaen Provincial Administrative Organization with a local development plan and emphasizing public participation in management at every step. 2. The problem in providing public services of the Khon Kaen Provincial Administrative Organization is the budget that has been allocated. Not enough to meet the needs of the people to operate in accordance with the various missions. and comments on organizational management for convenience and speed. 3. The level of public opinion towards the provision of public services according to the local development plan under the national strategy of the Khon Kaen Provincial Administrative Organization Overall, it's at a high level. by the Khon Kaen Provincial Administrative Organization Development strategies have been formulated according to the local development plan of the Khon Kaen Provincial Administrative Organization. There are systems and mechanisms for public administration that are consistent with their missions, enabling people to receive services in the provision of public services of the Khon Kaen Provincial Administrative Organization.